Evaluation of video review tools for assessing non-technical skills in emergency department resuscitation teams: a systematic review - Emily G Alexander; Fraser Denny; Malcom WG Gordon; Cieran McKiernan; David J Lowe (BMC Emergency Medicine, 2023)
Abstract Background and importance Use of video review in medicine is established in contexts such as surgery. Although not widely used in the emergency department (ED), some centres use it to evaluate non-technical skills (NTS) to support teaching and quality improvement. Objective There is no consensus on assessment of NTS using video review in the ED and the purpose of this review was to identify tools used in this context. Design, setting and participants Studies were identified using Embase, Medline, CINAHL and Google Scholar. Inclusion criterion for the review was NTS of resuscitation teams working within the ED were assessed using video review. A systematic search method was used, and results were synthesised after search criteria was checked by two independent reviewers. Authors settled on the same 9 studies eligible for inclusion. Outcome measures and analysis Reliability and validity of tools identified for use in this context. Due to the heterogeneity of studies, no meta-analysis occurred. Main results There are 9 studies included in the review. The review was registered with PROSPERO (Ref No: CRD42022306129). Four unique tools were identified – 6 studies used T-NOTECHS, 1 used TTCA-24, 1 used CALM and 1 used the Communication tool. T-NOTECHS is validated in the literature for use in this context. Conclusion T-NOTECHS is the tool of choice for assessing ED teams in this context.